2017
DOI: 10.1253/circj.cj-16-0904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes After Transcatheter vs. Minimally Invasive Cardiac Surgery Closure for Atrial Septal Defect

Abstract: nickel allergy. 6, 7 Technological advances have made contemporary surgery less invasive than classical surgery using full sternotomy. Cardiac surgery performed without full sternotomy is called minimally invasive cardiac surgery (MICS). 8 Advantages of MICS are swift recovery and reduction of pain and sternal wound infection. Furthermore, it is cosmetically appealing, considering the higher prevalence of women and the relatively young population of patients with ASD compared with the typical surgical populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
(33 reference statements)
0
22
0
2
Order By: Relevance
“…The patients with more than moderate and persistent tricuspid insufficiency after ASD closure have poor prognosis 22, 23. In our 7 patients with more than moderate TR that underwent TV Repair, tricuspid regurgitation severity became trivial to mild in postoperative period.…”
Section: Discussionmentioning
confidence: 67%
“…The patients with more than moderate and persistent tricuspid insufficiency after ASD closure have poor prognosis 22, 23. In our 7 patients with more than moderate TR that underwent TV Repair, tricuspid regurgitation severity became trivial to mild in postoperative period.…”
Section: Discussionmentioning
confidence: 67%
“…Patients were assessed immediately after and during follow-ups using colour Doppler flow imaging. 22 Aside from Kodaira et al 23 shunts were reported in 1180 adults across five studies (Table 3). [20][21][22]24,25 The studies are separated based on children or adults, with an overall risk ratio of a resulting minor residual shunt displayed (RR = 6.04, 95% CI 1.69-21.63 in favour of MIS approach, I 2 = 39.0%) (Figure 4).…”
Section: Results Of Interventionsmentioning
confidence: 93%
“…The characteristics of the six included studies are summarised in Table 1. [20][21][22][23][24][25] It is worth noting that the studies were all single centred and had a variable mean patient age. This difference in mean ages was accounted for during data analysis.…”
Section: Results Of the Searchmentioning
confidence: 99%
See 2 more Smart Citations